2018
DOI: 10.1515/biol-2018-0025
|View full text |Cite
|
Sign up to set email alerts
|

16S ribosomal RNA-based gut microbiome composition analysis in infants with breast milk jaundice

Abstract: BackgroundThis case-control study investigated an association between breast milk jaundice (BMJ) and infants’ gut microbiome. The study included determination of the diversity of the gut microbiome and identification of bacterial genera associated with BMJ.MethodsThe study population consisted of 12 infants with BMJ and 22 breastfed infants without jaundice (control). DNA collected from feces was analyzed by PCR amplification and 1% agarose gel electrophoresis, and then sequenced with a MiSeq system. Relative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 41 publications
(18 reference statements)
1
7
1
Order By: Relevance
“…When the abundance of E. coli in the intestine is elevated, the production of β-GD increases accordingly, which then increases bilirubin enterohepatic circulation and causes jaundice. However, Miao et al found that the proportion of Escherichia in normal healthy infants was 64.67%, which was significantly higher compared to those observed in BMJ infants (14). The results contrast with what we observed in this study.…”
Section: Discussioncontrasting
confidence: 99%
“…When the abundance of E. coli in the intestine is elevated, the production of β-GD increases accordingly, which then increases bilirubin enterohepatic circulation and causes jaundice. However, Miao et al found that the proportion of Escherichia in normal healthy infants was 64.67%, which was significantly higher compared to those observed in BMJ infants (14). The results contrast with what we observed in this study.…”
Section: Discussioncontrasting
confidence: 99%
“…The high proportion of Escherichia-Shigella may be attributed to the high content of Escherichia coli, which is part of the normal intestinal flora in newborns after birth and the most abundant bacteria in the first year, which was harmless under certain conditions (Taddei et al 2014). However, our previous study showed that the proportion of Escherichia-Shigella (genus level) in the gut microbiome was significantly higher in the control group than in the BMJ group (Duan et al 2018) The difference in the abovementioned results may be due to the different locations with different cooking cultures where the samples were collected.…”
Section: Resultsmentioning
confidence: 93%
“…However, our previous study showed that the proportion of Escherichia–Shigella (genus level) in the gut microbiome was significantly higher in the control group than in the BMJ group (Duan et al . 2018). Previous studies have demonstrated that a wide range of health and environmental factors including medication‐, diet‐ and health‐related variables and intrinsic factors are associated with changes in the composition and functionality of the gut microbiota (Falony et al .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations